Overview of the side-effects of FDA-and/or EMA-approved targeted therapies for the treatment of hematological malignancies - Constantinescu, Catalin; Pasca, Sergiu; Zimta, Alina-Andreea; Tat, Tiberiu; Rus, Ioana; Teodorescu, Patric; Iluta, Sabina; Tanase, Alina; Colita, Anca; Sigurjonsson, Olafur; Einsele, Hermann; Tomuleasa, Ciprian (Journal of Clinical Medicine, 2020)
In the last decade there has been tremendous effort in offering better therapeutic management strategies to patients with hematologic malignancies. These efforts have ranged from biological to clinical approaches and resulted in the rapid development of new approaches. The main “problem” that comes with the high influx of newly approved drugs, which not only influences hematologists that frequently work with these drugs but also affects other healthcare professionals that work with hematologists in patient management, including intensive care unit (ICU) physicians, is they have to keep up within their specialty and, in addition, with the side-effects that can occur when encountering hematology-specific therapies. Nonetheless, there are few people that have an in-depth understanding of a specialty outside theirs. Thus, this manuscript offers an overview of the most common side-effects caused by therapies used in hematology nowadays, or that are currently being investigated in clinical trials, with the purpose to serve as an aid to other specialties. Nevertheless, because of the high amount of information on this subject, each chapter will offer an overview of the side-effects of a drug class with each reference of the section being intended as further reading.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Hematological malignancies; Life-threatening side-effects; Novel therapies